External crises and family social capital reconfiguration: Insights from the European debt crisis and the Covid-19 pandemic - Hadjielias, Elias; Hughes, Mathew; Scholes, Louise (My University, 2022)
Drawing on 62 interviews with 23 family businesses in Cyprus concerning the 2013–2018 (Eurozone) debt crisis and the Covid-19 pandemic, this study offers new knowledge on why and how family social capital reconfigures during external crises to support survivability. The findings reveal new psychological and situational mechanisms motivating structural and relational changes in family social capital during crises. However, we find nuances and complexities acting on the motives and content of these changes, attuned to the type of external crisis that the family business faces. We contribute a context-sensitive theory of family social capital’s reconfiguration during external crises.